The Climate Effect on COVID-19: Lessons Learned from the Pandemic in Jakarta - Saki, Vernonia Yora; Deniati, Ema Novita; Saputra, Yoerdy Agusmal; Susanna, Dewi; Efendi, Efendi (Kesmas, 2023)
The global COVID-19 pandemic has presented humanity with difficult and unforeseeable hurdles. Among these challenges is understanding how climate-related aspects impact the survival of the SARS-CoV-2 virus. This study aimed to investigate the relationship between environmental factors, such as temperature, humidity, and rainfall, and the spread of COVID-19 cases in different regions. A time-and-place-based ecological study design was adopted, integrating geographic information systems and statistical techniques. Statistical testing revealed a significant association between humidity (p-value = 0.000; r = -0.777) and rainfall (p-value = 0.001; r = -0.561) with COVID-19 instances. However, no statistically significant relationship was found between temperature variables and COVID-19 cases. Due to the impact of changing weather conditions, governments may become concerned about developing tailored preventive and control measures, considering the varying risk levels associated with different locations.